Bilateral orthogonality generative acquisitions method for homogeneous T 2 images using parallel transmission at 7 T - Boğa, Çelik; Henning, Anke (Magnetic resonance in medicine, 2025)
The novel bilateral orthogonality generative acquisitions method has been developed for homogeneous images without the effects of transmit field inhomogeneity using a parallel-transmission (pTx) system at 7 T. A new method has been introduced using four low-angle gradient-echo (GRE) acquisitions to obtain homogeneous contrast by removing the effects of transmit field inhomogeneity in the pTx system. First, two input images are obtained in circularly polarized mode and another mode in which the first transmit channel or channel group have an additional transmit phase of π. The last two acquisitions are single-channel acquisitions for a dual-channel system or single-channel group acquisitions for more than two channels. The introduced method is demonstrated in dual-channel and eight-channel pTx systems using phantom and whole-brain in vivo experiments. Noise performance of the proposed method is also tested against the ratio of two GRE acquisitions and the TIAMO (time-interleaved acquisitions of modes) method. Th new method results in more homogeneous contrast in the final images than the compared methods, particularly in the low-intensity regions of circularly polarized-mode images for the images obtained via ratio of the two GRE acquisitions. The introduced method is easy to implement, robust, and provides homogeneous images of the whole brain using pTx systems with any number of channels, compared with the ratio of the two GRE images and the TIAMO method.